Clinical and Economic Burden of Peristomal Skin Complications in Patients With Recent Ostomies. Issue 4 (July 2017) - Taneja, Charu; Netsch, Debra; Rolstad, Bonnie Sue; Inglese, Gary; Lamerato, Lois; Oster, Gerry
Abstract : PURPOSE: The purpose of this study was to estimate the risk and economic burden of peristomal skin complications (PSCs) in a large integrated healthcare system in the Midwestern United States. DESIGN: Retrospective cohort study. SUBJECTS AND SETTING: The sample comprised 128 patients; 40% (n = 51) underwent colostomy, 50% (n = 64) underwent ileostomy, and 10% (n = 13) underwent urostomy. Their average age was 60.6 ± 15.6 years at the time of ostomy surgery. METHODS: Using administrative data, we retrospectively identified all patients who underwent colostomy, ileostomy, or urostomy between January 1, 2008, and November 30, 2012. Trained medical abstractors then reviewed the clinical records of these persons to identify those with evidence of PSC within 90 days of ostomy surgery. We then examined levels of healthcare utilization and costs over a 120-day period, beginning with date of surgery, for patients with and without PSC, respectively. Our analyses were principally descriptive in nature. RESULTS: The study cohort comprised 128 patients who underwent ostomy surgery (colostomy, n = 51 [40%]; ileostomy, n = 64 [50%]; urostomy, n = 13 [10%]). Approximately one-third (36.7%) had evidence of a PSC in the 90-day period following surgery (urinary diversion, 7.7%; colostomy, 35.3%; ileostomy, 43.8%). The average time from surgery to PSC was 23.7 ± 20.5 days (mean ± SD). Patients with PSC had index admissions that averaged 21.5 days versus 13.9 days for those without these complications. Corresponding rates of hospital readmission within the 120-day period following surgery were 47% versus 33%, respectively. Total healthcare costs over 120 days were almost $80, 000 higher for patients with PSCs. CONCLUSIONS: Approximately one-third of ostomy patients over a 5-year study period had evidence of PSCs within 90 days of surgery. Costs of care were substantially higher for patients with these complications.